Influence of Age and Gender on Levels of Knowledge of Anambra Motor Manufacturing Company (ANAMCO) Workers towards Occupational Health Hazard - Dorothy I. Ugwu , Dorothy I. Ugwu (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
The study explored the level of knowledge of ANAMCO workers regarding occupational health hazards. Two null hypotheses were tested at 0.05 level of significance. A total number of 521 workers of ANAMCO constituted the population for the study. The sample for the study was 261 workers selected by means of stratified sampling technique. The instrument used for the study was Knowledge of Occupational Health Hazard (KOHH) questionnaire, which was developed by the researcher. Frequency, percentages and chi-square statistics were adopted for data analysis. Result revealed that younger workers reported higher knowledge than older workers; male workers reported higher knowledge than the female workers. There are significant differences in the levels of knowledge of workers, with younger workers differing significantly higher than the older workers and the males differing significantly higher than the females. It was recommended, among others, that management of ANAMCO should try to show more commitment to the training and organisation of knowledge oriented programmes. This will help equip workers on knowledge regarding hazards associated with their jobs.